2021
DOI: 10.3390/microorganisms9020421
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antimicrobials Suitable for Combating Desiccation-Resistant Salmonella enterica in Milk Powder

Abstract: Some Salmonella enterica strains survive well in low-water activity (low-aw) foods and cause frequent salmonellosis outbreaks in these products. Methods are needed to overcome such desiccation-resistant Salmonella and to improve the safety of low-aw foods. Building on a recent finding, we hypothesized that natural antimicrobial food additives, which are active against cytoplasmic membrane, could overcome this desiccation resistance phenomenon, and thus, sensitize the pathogen to drying and mild processing. Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The preparation of desiccation-adapted dry cells of Salmonella Tennessee was performed as reported in previous studies [9,11], described in the materials and methods section, and demonstrated in Figure 1. The desiccation-adapted cells were used in various experiments after resuspension in different media as required in each experiment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The preparation of desiccation-adapted dry cells of Salmonella Tennessee was performed as reported in previous studies [9,11], described in the materials and methods section, and demonstrated in Figure 1. The desiccation-adapted cells were used in various experiments after resuspension in different media as required in each experiment.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that carvacrol and thymol are candidate food additives to combat desiccation-resistant Salmonella, in view of their activity against bacterial cytoplasmic membranes. In a previous study, the two additives sensitized desiccation-adapted Salmonella to heating at 55 • C for 15 min [11]. Furthermore, the anti-Salmonella effect of carvacrol was apparent during sprayor freeze-drying of liquid milk, and this effect was noticeable during storage of the dried milk at room temperature [11].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations